Preparing for the future of work: a novel data-driven approach for the identification of future skills - Julia Brasse; Maximilian Förster; Philipp Hühn; Julia Klier; Mathias Klier; Lars Moestue (Journal of Business Economics, 2023)
The future of work is changing rapidly as result of fast technological developments, decarbonization and social upheavals. Thus, employees need a new skillset to be successful in the future workforce. However, current approaches for the identification of future skills are either based on s small sample of expert opinions or the result of researchers interpreting the results of data-driven approaches and thus not meaningful for the stakeholders. Against this background, we propose a novel process for the identification of future skills incorporating a data-driven approach with expert interviews. This enables identifying future skills that are comprehensive and representative for a whole industry and region as well as meaningful for the stakeholders. We demonstrate the applicability and utility of our process by means of a case study, where we identify 33 future skills for the manufacturing industry in Baden-Wuerttemberg, Germany. Our work contributes to the identification of comprehensive and representative future skills (for whole industries).
Keywords: J24; M00; 650; Future skills; Future skill identification; Job advertisement analysis; Case Study